Kesibukan Organisasi dan Ilusi Efektivitas: Analisis terhadap Produktivitas Semu dalam Pengelolaan Lembaga Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Organizational busyness in Islamic educational institutions does not necessarily indicate effective management, particularly when high levels of managerial activity are not accompanied by commensurate outcomes. This study aims to analyze pseudo-productivity in the management of Islamic educational institutions by examining the relationship between organizational activity intensity, decision-making, and execution capacity. The study employs a qualitative approach using a literature review method. Data were obtained from scholarly journal articles, academic books, and previous studies relevant to organizational effectiveness, productivity, decision implementation, organizational learning, strategic management, and Islamic educational management. Data were analyzed through qualitative content analysis and conceptual synthesis to identify patterns linking managerial activities with institutional outcomes. The findings reveal two major issues. First, the high frequency of meetings, programs, coordination activities, and administrative tasks may create a perception of productivity that does not necessarily reflect substantive organizational effectiveness, as success is often assessed in terms of activity completion rather than the changes produced. Second, weak follow-up mechanisms, unclear ownership of decisions, limited monitoring, and the absence of measurable implementation indicators create a gap between decisions and actions. This condition may generate recurring organizational problems and increase the institutional workload without producing proportional improvements. The study emphasizes the need to shift from activity-oriented management toward outcome-oriented management by strengthening execution mechanisms, accountability, monitoring, and continuous improvement. Ultimately, the effectiveness of Islamic educational institutions is determined not by how busy the organization appears to be, but by the extent to which its activities generate meaningful changes that contribute to the achievement of institutional goals.